2010
DOI: 10.1002/oti.300
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a motor‐based, social skills intervention for adolescents with high‐functioning autism: two single‐subject design cases

Abstract: The purpose of this study was to assess the effect of a motor-based, social skills intervention for two adolescents with high-functioning autism (HFA) using single-subject design. A description of the intervention is provided as a first step in the manualization process. The intervention was provided as a 7-week after-school program, once weekly to the paired participants. Intervention consisted of role-play methods in which motor behaviours were linked with their cognitive and emotional meanings. Baseline, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 28 publications
(27 reference statements)
1
17
0
Order By: Relevance
“…This study also addressed the concerns of Gutman et al related to the cognitive demand of computer-based motor intervention [13]. Most participants demonstrated significant improvement in executive functioning skills.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…This study also addressed the concerns of Gutman et al related to the cognitive demand of computer-based motor intervention [13]. Most participants demonstrated significant improvement in executive functioning skills.…”
Section: Discussionmentioning
confidence: 85%
“…Mirror neurons may underlie the basis for how humans learn to connect motor behavior with cognitive and emotional intention [11][12]. For example, Gutman et al stated, "mirror neurons may allow us to see a motor behavior and link it to the cognitive and emotional intention of the performer" [13].…”
Section: Mirror Neuronsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inclusion of a probe phase (Finnigan & Starr, 2010;Gutman, et al, 2010), in which we resumed the repeated observation after a break, provided an option for long-term follow up of the target behavior. A probe phase maintains the integrity of the repeated measurement, by extending the period over which outcomes are measured.…”
Section: Probe Phasementioning
confidence: 99%
“…Motor-based interventions are also an important OT technique as it has been proposed that autistics might have a deficiency in their mirror neuron systems, which monitor the appropriate motor, social and emotional responses to performing an action or perceiving others perform an action. Single-subject studies have, in fact, shown an overall improvement in social and emotional skills and behaviours after the introduction of a motor-based social skills intervention 27,28 . Even physical activities such as yoga have been shown to have a significant improvement in social and challenging behaviours in autistic individuals 29 .…”
Section: Occupational Therapymentioning
confidence: 99%